Nonlinear optical excitation response and regulation of instabilities in a Y-type atomic system under complex interactions - Shang-Yu Zhai; Rui Shi; Fu-Han Xie (AIP Advances)
In this work, a Y-type energy level ensemble of an alkali metal Rydberg rubidium cold atomic system under complex interactions is considered. To solve this nonlinear optical response, Newton’s iterative method is employed with random initial values for solving the multi-body density matrix equations and further observing the Rydberg excitation’s instability. The effects of self-interaction and direct and exchange interactions in the cross-interactions are comprehensively considered via three real cases: (I) only self-interaction; (II) self-interaction and direct interaction; and (III) self-interaction, direct interaction, and exchange interaction simultaneously. The results indicate that under the condition of I, since the system only has self-interaction, it exhibits only a typical bistable phenomenon. With the introduction of direct interaction, the Rydberg population in II shows a bifurcated bistable phenomenon. Finally, a more complex exchange interaction is further introduced. Under the condition of III, the system exhibits a complex multi-stable phenomenon in the same detuning direction. More importantly, such bistable and multi-stable phenomena can be well regulated by changing the cooperative nonlinearity modulated via the pump field. In addition, the bistable and multi-stable atomic excitation responses of the system on one transition branch can also be controlled by the coupling field Rabi frequency on another transition branch. This work applies numerical iterative algorithms to achieve a detailed analysis of the new phenomena with bistable and multi-stable excitation responses for nonlinear characteristics and provides theoretical support for the preparation of optical multistable materials.